Methods and Systems for Allocating and Reporting Indirect Costs in Management Accounting - Simeonova, R. (Економічний вісник Донбасу, 2015)
One of the main issues in management accounting, which has always been topical, and for which solutions are sought in its theory and practice, refers to the allocation and reporting of indirect costs. Indirect costs are an important element of cost under the current conditions. The paper discusses the importance of cost both in financial and management accounting - especially regarding cost management in different directions. Under the present conditions, there is an increase in the share of indirect costs in the cost of manufactured goods and services. This is inevitably associated with their allocation, which as a rule is provisional. The current paper studies the various methods and models of allocating indirect costs: the method of coefficients; the method of cost analysis centres and “Direct costing” system. The search for opportunities to improve the allocation of these costs is related to the Activity-based costing method (ABC). The paper studies the conceptual foundations and guidelines for its application.